Da rugiada a ruggine. Poesia dialettale e ambiente: Pasolini, Zanzotto, De Vita - Malicka, Paulina (Studia Romanica Posnaniensia, 2022)
The scope of the present article is to reflect upon the question of the environment within the context of the discussion concerning the use of dialect in the poetry of Pier Paolo Pasolini, Andrea Zanzotto, Nino De Vita and other poets from Sicily. Commencing from the concept of ‘diversity’, as intended by Pasolini as the disappearance of the rural world, which occurs in step with the eclipses of dialectal variety, the essay will demonstrate how the environment – the crucial focus of the poetry of the above mentioned poets – converges concepts of dialects, territoriality and animality. The ecocritical method, which is applied in this study, enables one to signal the urgency to reflect upon the situation of contemporary poetry, in particular of Sicilian poetry, which has its roots in Nino De Vita’s poetic works, inextricably tied to the place, the natural and the cultural context of the island. The new Sicilian poetry does not cancel ‘diversity’, which on the contrary is capable of confronting environmental issues – at times also beyond the island’s borders – and it feeds from the lymph, from the root of the dialect.